2013
DOI: 10.1186/1479-5876-11-141
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protects against renal ischemia and reperfusion injury by inhibiting the JAK/STAT signaling activation

Abstract: BackgroundThe α2-adrenoreceptor agonist dexmedetomidine is known to provide renoprotection against ischemia and reperfusion (I/R) injury. However the underlying molecular mechanisms remain unclear. The purpose of this study was to investigate whether the Janus kinase and signal transducer and activator of transcription (JAK/STAT) signaling pathway plays a role in dexmedetomidine’s renoprotection.MethodsI/R model was induced by bilateral renal pedicle clamping for 45 min followed by 48 h of reperfusion in male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 48 publications
8
114
0
Order By: Relevance
“…In another study, it has been observed that the dex application reduces kidney caspase 3, plasma ICAM-1 and monocyte chemo attractant protein-1 (MCP-1) levels; and these effects have been inhibited by atipamezole, which is a-2 antagonist. 19 These results suggest that the dex causes these effects through a-2 adrenergic receptors.…”
Section: Discussionmentioning
confidence: 86%
“…In another study, it has been observed that the dex application reduces kidney caspase 3, plasma ICAM-1 and monocyte chemo attractant protein-1 (MCP-1) levels; and these effects have been inhibited by atipamezole, which is a-2 antagonist. 19 These results suggest that the dex causes these effects through a-2 adrenergic receptors.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies have showed that dexmedetomidine could reduce the renal I/R injury, by inhibiting Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway 4 or activating cell survival signal p-AKT 5 . Koca et al 14 showed that dexmedetomidine also attenuated sepsis-induced kidney injury and apoptosis in the rat model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The dose (50 μg/kg, i.p.) referred to previous literature in rats 4,14 . Whether the larger dose of dexmedetomidine decreases renal I/R injury under hyperglycemia may need to be elucidated in further research.…”
Section: Acute Hyperglycemia Prevents Dexmedetomidine-induced Precondmentioning
confidence: 99%
See 1 more Smart Citation
“…The Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway plays a critical role in cytokine production mediating IRI 19. Dexmedetomidine, an α2‐adrenoreceptor agonist, inhibits the phosphorylation of JAK/STAT proteins, and has proved to be an effective agent in slowing the progression of renal IRI in rodents 20. Upstream of the JAK/STAT pathway lies nuclear factor kappa B (NF‐κB), a transcription factor that has also been shown to regulate the inflammatory cascade in IRI.…”
Section: Ischemia‐reperfusion Injurymentioning
confidence: 99%